2016
DOI: 10.1038/srep38477
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative HDL Proteomics Identifies Peroxiredoxin-6 as a Biomarker of Human Abdominal Aortic Aneurysm

Abstract: High-density lipoproteins (HDLs) are complex protein and lipid assemblies whose composition is known to change in diverse pathological situations. Analysis of the HDL proteome can thus provide insight into the main mechanisms underlying abdominal aortic aneurysm (AAA) and potentially detect novel systemic biomarkers. We performed a multiplexed quantitative proteomics analysis of HDLs isolated from plasma of AAA patients (N = 14) and control study participants (N = 7). Validation was performed by western-blot (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 49 publications
(57 reference statements)
0
25
0
Order By: Relevance
“…Downloaded from http://ahajournals.org by on April 30, 2019 in the pathogenesis of AAA. 25,31 Interestingly, in a previous study of 10 patients, peroxiredoxin-1 was found to be increased in the luminal compared with the abluminal part of the ILT. 24 The abundant erythrocytes in the luminal part of the ILT deliver an endless supply of cells that generate reactive oxidative species.…”
Section: -mentioning
confidence: 87%
“…Downloaded from http://ahajournals.org by on April 30, 2019 in the pathogenesis of AAA. 25,31 Interestingly, in a previous study of 10 patients, peroxiredoxin-1 was found to be increased in the luminal compared with the abluminal part of the ILT. 24 The abundant erythrocytes in the luminal part of the ILT deliver an endless supply of cells that generate reactive oxidative species.…”
Section: -mentioning
confidence: 87%
“…For example, advances in proteomics have extended the list of HDL-associated proteins, beyond the apolipoproteins associated to HDL, to over 85 suggesting that the composition of HDL is more complex than previously anticipated [69]. Studies have also shown that the levels of specific HDL-associated proteins are altered in disease states [86,87] and in polluted environments [88], and could therefore potentially also be used as disease biomarkers [89]. LDL and VLDL are also associated with a growing number of associated proteins that are known to have important functions in dyslipidemia, atherosclerosis, and coagulation disorders [90].…”
Section: Evs and Lipoproteins As Biomarkersmentioning
confidence: 99%
“…Prdx6 content in blood serum was increased in ~50% of patients with Crohn's disease (161). Tissue and plasma levels of Prdx6 have been proposed as a biomarker for human abdominal aortic aneurysm (162). Lung…”
Section: Other Pathophysiologymentioning
confidence: 99%